The effect of brisk walking on postural stability, bone mineral density, body weight and composition in women over 50 years with a sedentary occupation: a randomized controlled trial - Gába, Aleš; Cuberek, Roman; Svoboda, Zdeněk; Chmelík, František; Pelclová, Jana; Lehnert, Michal; Frömel, Karel (BMC women's health, 2016)
BACKGROUND: To assess the effect of brisk walking on postural stability, bone mineral density (BMD) and body composition in women over 50 years of age with a sedentary occupation. METHODS: A 10-week walking intervention based on self-regulated brisk walking (BW) to or from work of 30-35 min at least 5 times per week. The research included a total of 104 women (58 women in intervention group). The mean center of pressure (COP) velocity in medial-lateral and anterior-posterior directions, mean total COP velocity with eyes open and closed, BMD of the distal forearm and the calcaneus, body weight, fat mass, and lean body mass were assessed. RESULTS: The BW intervention was completed by 76 % of participants. A significant effect (time × group interaction) was confirmed only in the mean COP velocity in the anterior-posterior direction with eyes closed (F = 7.41, P = 0.008). The effect of BW was not confirmed in BMD, body weight, or body composition. The results indicate that the effect of the intervention is influenced by baseline body mass index in body weight, fat mass and visceral adipose tissue. CONCLUSIONS: BW prevents the deterioration of postural stability with eyes closed, which can have a direct effect on reducing the risk of falls under worse spatial orientation and visibility. The presented intervention model is insufficient for weight loss, changes in BMD, or body composition, and its effect should be assessed during a longer period of time. TRIAL REGISTRATION: German Clinical Trials Register DRKS00007638 , registered March 10, 2015 (retrospectively registered).
Keywords: Body composition; Obesity; Osteoporosis; Falls; Walking intervention; Pedometer